Risk of Anterior Cruciate Ligament Fatigue Failure Is Increased by Limited Internal Femoral Rotation During In Vitro Repeated Pivot Landings - Beaulieu, Mélanie L. (Am J Sports Med, 2015)
BACKGROUND: A reduced range of hip internal rotation is associated with increased peak anterior cruciate ligament (ACL) strain and risk for injury. It is unknown, however, whether limiting the available range of internal femoral rotation increases the susceptibility of the ACL to fatigue failure. HYPOTHESIS: Risk of ACL failure is significantly greater in female knee specimens with a limited range of internal femoral rotation, smaller femoral-ACL attachment angle, and smaller tibial eminence volume during repeated in vitro simulated single-leg pivot landings. STUDY DESIGN: Controlled laboratory study. METHODS: A custom-built testing apparatus was used to simulate repeated single-leg pivot landings with a 4×-body weight impulsive load that induces knee compression, knee flexion, and internal tibial torque in 32 paired human knee specimens from 8 male and 8 female donors. These test loads were applied to each pair of specimens, in one knee with limited internal femoral rotation and in the contralateral knee with femoral rotation resisted by 2 springs to simulate the active hip rotator muscles’ resistance to stretch. The landings were repeated until ACL failure occurred or until a minimum of 100 trials were executed. The angle at which the ACL originates from the femur and the tibial eminence volume were measured on magnetic resonance images. RESULTS: The final Cox regression model (P = .024) revealed that range of internal femoral rotation and sex of donor were significant factors in determining risk of ACL fatigue failure. The specimens with limited range of internal femoral rotation had a failure risk 17.1 times higher than did the specimens with free rotation (P = .016). The female knee specimens had a risk of ACL failure 26.9 times higher than the male specimens (P = .055). CONCLUSION: Limiting the range of internal femoral rotation during repetitive pivot landings increases the risk of an ACL fatigue failure in comparison with free rotation in a cadaveric model. CLINICAL RELEVANCE: Screening for restricted internal rotation at the hip in ACL injury prevention programs as well as in individuals with ACL injuries and/or reconstructions is warranted.